La comisión contra la impunidad en Guatemala. Tendencias hacia un Derecho Penal Internacional híbrido en Centroamérica - García Azofeifa, Ignacio (2014)
On December 12, 2006, the United Nations and the Government of Guatemala created the International Commission Against Impunity in Guatemala (CICIG). Its current commissioner is former Attorney General of Costa Rica, Francisco D’Allanese. This Commission is part of an unprecedented effort in the international community. The main objective of this article is to present a brief historical account that would allow Costa Rican lawyers understand the origins of CICIG, and anticipate the evolution it may experience in a near future.